Associations between local rates of violence and experiences of psychosis in Trinidad - Roberts, Tessa; Lee Pow, Joni; Donald, Casswina; Quattrone, Diego; Hutchinson, Gerard; Morgan, Craig (Frontiers in Public Health, 2025)
Introduction and aimIndividual-level exposure to violence is known to influence various aspects of the experience of psychosis. This study aimed to assess the impact of local violence rates on the symptom profiles and outcomes of people with psychosis, their exposure to trauma and other potential risk and protective factors, and interactions with the police and mental health services, in a Caribbean country with high rates of violent crime.MethodsData from 212 people with psychosis and matched population control participants were collected through a population-based programme of research on psychosis in Trinidad (INTREPID II) and linked geographically with crime statistics, disaggregated to the areas surrounding each police station.ResultsThere was no evidence of a substantive association between local rates of violent crime and symptoms of psychosis or the course of illness on most measures, although people in lower crime areas appeared to be more likely to experience hallucinations than those living in high-violence areas (β-0.30, 95% CI −0.50–−0.11, p < 0.01). There was some evidence that people living in high-violence areas were more likely to be restrained within the mental health system than those from lower-violence areas (OR 2.00, 95% CI 0.98–4.09, p = 0.06), despite being no more likely to act in violent or disruptive ways.ConclusionThe lack of association between violent crime and various aspects of psychosis may indicate that the psychological effect of violent crime is not confined to single localities, and may be influenced by other factors besides rates of violence in participants’ immediate local area. Research is needed to investigate why individuals from disadvantaged neighbourhoods that are associated with gang violence experience different treatment within health services and to evaluate strategies to address these disparities.